Brief mindfulness practice as an intervention on the relationship between cyberbullying and depressive symptom among young adults in Malaysia - Choo, Benjamin Bing Chee; Lee, Ziyi; Ng, Jun Quan (2019)
This paper reviews whether the role of mindfulness practice could reduce depressive symptoms caused by cyberbullying experience. Seventy-two participant were recruited and randomly assigned into experimental group or control group. Cyberbullying victimization was manipulated through the uses of threatening, harassing, insulting and teasing sentences in the game named “Roblox”. Control group did not undergo any manipulation. Cyberbullying victimization, depression, stress and anxiety score were recorded after the game. Participant in experimental group will then watch a mindfulness practice video (S.T.O.P) whereas control group will watch a TED talk video. After the video, depression, stress, anxiety and state mindfulness score were recorded. Result shows that there are significant differences in the cyberbullying victimization score of experimental group and control group after the game. Indicating that participant in the experimental group felt cyberbullied after the game. Although cyberbullying victimization was induced among experimental group, no significant differences was found in the depression, stress, anxiety and level when compared with control group. It was assumed that cyberbullying victimization manipulation was not strong enough to create a significant difference because some participant feedback that they are used to the cyberbullied message while some mentioned that attention was given in learning how to play the game. Within experimental group, there is significant decrease in the score of depression and stress before and after the mindfulness practice video (S.T.O.P). Findings in this study can be used as a possible treatment for Exposure Therapy in early cyberbullying exposure.